DETERMINANTS OF PROFITABILITY AND DEA EFFICIENCY ANALYSIS OF INDONESIA’S CIGARETTE INDUSTRY - Setiawan, Chandra; Angelina, Selly (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
Despite high smoking rates and large household spending on cigarettes, the cigarettesales volume in Indonesia has gradually declined. Due to challenging years in thecigarette industry, this research aims to analyze the determinants of profitability andefficiency of cigarette companies in Indonesia from 2019 to 2023. The study uses datafrom quarterly financial reports of four companies listed on the IDX. In panel dataregression analysis, the independent variables include the current ratio (CR), assetturnover (TATO), and debt-to-equity ratio (DER), while the dependent variable is returnon assets (ROA). The selected model is the Fixed Effect Model (FEM). The findings revealthat CR and DER significantly negatively influence return on assets, whereas TATO hasa significant positive influence on ROA. All the independent variables collectively have asignificant influence on the ROA of cigarette companies. Among these variables, DERhas the most significant influence on profitability. These variables explain 51.90% of thevariation in ROA. Separately, the average technical efficiency score of cigarettecompanies in Indonesia from 2019 to 2023 is 69.0%. Simple regression analysis showsthat the average technical efficiency score is positive and significantly influences ROA.This variable explains 47.68% of the variation in ROA. Overall, these variables in thisresearch explain 99.76% of the variation in ROA. In conclusion, cigarette companiesshould prioritize using their assets effectively and carefully manage debt levels to attractinvestors and maintain stable returns even during market fluctuations.Keywords: Profitability, Efficiency, Cigarette Companies